Fatigue failure analysis of rotor compressor blades concerning the effect of rotating stall and surge. (October 2016) - Luo, Shuai; Wu, Sujun
Abstract: Detailed investigation was performed on the effect of the rotating stall and surge on the fatigue failure mechanisms of the axial compressor first stage rotor blades. The static stress distribution of the blades was analysed using three dimensional (3D) finite element method (FEM). The critical fracture stress was calculated using the linear elastic fracture mechanics. Fractographic observation revealed different fatigue fracture modes corresponding to the different fatigue loads. Results demonstrated that during operation two kinds of fatigue loads can occur which are tension-torsion fatigue and bending fatigue. The tension-torsion fatigue stems from the periodic tension-torsion stress induced by the surge, while the bending fatigue load is caused by the rotating stall. Highlights: Different fatigue fracture mechanisms of the blades were identified. The static stress of the blades was analysed using 3D finite element method (FEM). The critical fracture stress of the blade at failure position was calculated. The effect of the rotating stall and surge on fatigue modes was explained.